The Influence of Climate Factors on the Incidence Area of Fusarium spp. in Shallots on Java Island during the Triple-Dip La Niña (2020-2022) - Dharma, Krisnanda Surya (Jurnal Perlindungan Tanaman Indonesia, 2024)
Shallots are a strategic horticultural commodity that contributes to inflation in Indonesia. The productivity of shallots is vulnerable to pests and diseases. Based on the incidence area during the La Niña period (2020 – 2022), Fusarium spp. is among the top five main pests and diseases reported to attack shallot crops in Java. Climate factors are suspected to have an effect on diseases incidence in the field. So far, there has been no research on the influence of climate factors on Fusarium twisted disease in Java. This study aims to analyze the influence of climate factors on the monthly incidence area of Fusarium spp. in Java during the La Niña period (2020 – 2022). The analysis used correlation and simple linear regression tests. Based on the correlation test, humidity and precipitation had a strong positive correlation with the incidence area of Fusarium spp. in shallots. Conversely, the sunshine duration had a strong negative correlation, while the temperature showed no correlation. From the simple linear regression test, humidity, precipitation and sunshine duration was found to strongly influence Fusarium spp. incidence, accounting for 47%, 48% and 40%, respectively (p<0.05). Temperature had no effect because it had the lowest fluctuation among other climate factors, ranging between 26 - 27.5°C, which was ideal for the development of Fusarium spp. To manage Fusarium spp. on shallots, it is recommended to select resistant varieties, optimize plant spacing, use fertilizers judiciously, and utilize healthy seeds. Additionally, the application of biological agents can suppress the growth of pathogenic fungi and increase plant resistance.